A Direct Comparison of Pilot-Scale Li-Ion Cells in the Formats PHEV1, Pouch, and 21700. Issue 9 (9th September 2021) - Waldmann, Thomas; Rössler, Stefan; Blessing, Markus; Schäfer, Robin; Scurtu, Rares-George; Braunwarth, Wolfgang; Wohlfahrt-Mehrens, Margret
Abstract : Li-ion cells of the industrially-relevant formats PHEV1 (prismatic), multi-layer pouch, and 21700 (cylindrical) are directly compared by experiments for the first time. All three cell formats were reproducibly built on pilot-scale with the same anode (graphite), cathode (NMC622), separator, and electrolyte allowing a direct comparison. The main differences between these formats are their capacities (24.6 Ah, 2.2 Ah, 2.3 Ah), volume/surface ratios, as well as tab and the jellyroll/stack configurations (flat-wound, stacked, wound). The comparison involves voltage curves during formation (0.1 C), discharge rate capability (0.5 C−3 C), heating behaviour, cell impedances, geometrical properties such as electrode curvatures and tab configurations, as well as comparison with coin half cells with anode and cathode vs Li counter electrode. The data are put into context with commercial and pilot-line built cells from other studies.